Increasing returns to scale and regions: a multilevel model for Brazil - Britto, Gustavo; McCombie, John S.L. (Brazilian Keynesian Review, 2015)
The paper proposes and tests an alternative way to incorporate a spatial dimension to the Verdoorn Law using multilevel models, tailored to deal with nested data. This methodology allows extending the Verdoorn equation, incorporating elements from Urban Economics to Post-Keynesian growth analysis. The estimations used firm-level data from the Brazilian manufacturing industry from 1996 to 2002. The results showed that, after controlling for firms’ characteristics, the spatial dimension is crucial to explain rates of labour productivity and output growth. Moreover, the estimations showed that substantial knowledge spillovers and urbanisation externalities are beneficial to firms’ growth, whereas localisation externalities tend to be harmful.